A cross‐sectional study of susceptibility to vaccine‐preventable diseases among prison entrants in New South Wales. Issue 7 (15th April 2013) - Larney, Sarah; Monkley, Denise L; Indig, Devon; Hampton, Stephen E
Abstract: Objectives: To determine the prevalence of susceptibility to measles, mumps, rubella, varicella and hepatitis B virus (HBV) among New South Wales prison entrants and to compare results for prison entrants with those of a community sample. Design and setting: Between 11 October 2010 and 24 October 2010, new entrants at seven adult correctional centres completed a cross‐sectional survey and provided a venous blood sample. Participants: All adults entering the correctional centres were eligible to participate, with 211 completing the survey (response rate 68%). Main outcome measures: Serological evidence of immunity to measles, mumps, rubella, varicella and HBV. Prison data were compared with community data obtained from the 2007 Australian National Serosurveillance Program. Results: Over half of the participants (106/204, 52%) were susceptible to HBV, followed by susceptibility to mumps (82/198, 41%), rubella (33/209, 16%), measles (27/203, 13%) and varicella (19/198, 10%). Having no history of drug injection was a significant predictor of susceptibility to measles, mumps and HBV. Prison entrants were significantly less likely than people in the community to be susceptible to varicella (10% versus 18%; risk ratio [RR], 1.9; 95% CI, 1.1–3.2) and HBV (52% versus 65%; RR, 1.3; 95% CI, 1.1–1.5). Conclusions: Prison entrants are susceptible to a number of vaccine‐preventable diseases. We recommend a cost–benefit analysis of implementing routine vaccination for measles, mumps, rubella and varicella and an exploration of options for improving uptake of HBV vaccination.